Video evidence and other information relevant to the conservation of the Ivory-billed Woodpecker (Campephilus principalis). Issue 1 (January 2017) - Collins, Michael D.
Abstract: Despite the publication of three independent papers that reported sightings of the Ivory-billed Woodpecker ( Campephilus principalis ), its preservation became a controversial topic because nobody has been able to obtain a distinct photo, which is considered the standard form of evidence for documenting birds. An analysis based on a combination of factors related to habitat and behavior suggests that the expected waiting time for obtaining a distinct photo of an Ivory-billed Woodpecker is several orders of magnitude greater than it would be for a more typical baseline species of comparable rarity. Given these difficulties and the time pressure involved to ensure the conservation of this species, this paper discusses the need to use a different approach for an exceptional case. Presented here are three videos that show birds with flights, behaviors, field marks, and other characteristics that are consistent with the Ivory-billed Woodpecker but no other species inhabiting the region.